The analysis of trait inheritance of rice hybrid from the crossing of the upland rice sample “Kontro” with the productive rice variety “Kuboyar” - P. I. Kostylev (Зерновое хозяйство России, 2020)
Rice is an important agricultural crop. It can grow not only when the flooded soil, but in the conditions of periodic irrigation, both artificial and natural (rain). The production of such rice is much cheaper. In addition, there is a shortage of fresh water in the world, which makes the use of upland rice relevant. The purpose of the current work was to develop the productive drought-resistant rice lines based on the “Kontro x Kuboyar” hybrid. The main tasks were to hybridize the varieties, to analyze genetically a number of quantitative traits and to select the best plants that could form compact full-grained panicles for further breeding work and testing for drought resistance. There has been conducted a genetic analysis of varying quantitative traits affecting the rice productivity. The parental forms did not differ in plant height. Along the panicle length there was a partial negative dominance and monogenic differences between the hybridized varieties. According to the number of spikelets per panicle there has been identified a negative dominance of lower values and the interaction of two pairs of genes. According to 1000 grain weight, there was a partial dominance of large values of the trait and monogenic differences in the original parental forms. Splitting along the length and width of the caryopsis was in a ratio of 1 : 2 : 1, which indicated monogenic differences between the parental varieties. There have been selected the best recombinant rice forms, combining a compact panicle with a large number of grains, and there has been developed the initial material for practical breeding. The study was carried out in 2019 on the plots of the Separate Subdivision “Proletarskoye” of the FSBSI “ARC “Donskoy” in the Rostov Region.